Designer patterned functional fibers via direct imprinting in thermal drawing - Zhe Wang (Nature Portfolio, 2020)
Creating micro/nanostructures on fibers is beneficial to many fiber-based devices, which remains a challenge in large-scale fabrication due to elongation and reflow. Here, the authors demonstrate a method for generating high-resolution, arbitrarily designed surface patterns on fiber during the thermal drawing process.